Análise ambiental da Bacia do Rio Prata : uma contextualização sobre produção do espaço geográfico nos sistemas de drenagem para o Pantanal Mato-grossense - Sales, Jepherson Correia (2017)
The intervention of man over nature for the production of geographical space has occurred without the proper concern to achieve the balance between the use of these goods and the dynamics of nature. In this bias, the context of land use from the 1960s in Brazil and the state of Mato Grosso was based on agricultural production, the result of the adoption of economic policies aimed at the occupation of the Brazilian west, associated with environmental physical possibilities (soil , Climate, relief and vegetation) suitable for large-scale monoculture planting to meet national and international demands related to agribusiness financial systems. The River Plate Basin (BHRP) is one of the areas affected by intensive land use for agricultural purposes, presenting environmental problems related to the unsustainable use of its area, such as soil loss due to erosion and gullies. The BHRP is located in the municipalities of Jaciara, Juscimeira and Santo Antônio do Leverger, it has 457.96 km², being between the coordinates: latitude: 16 ° 12'50.98 "S, longitude: 55 ° 23'1.76" W and latitude: 16 ° 6'30.45 "S, longitude: 54 ° 56'27.51" W, west-east direction. This is part of the northern portion of the Paraná Sedimentary Basin and is part of the São Lourenço River Basin, a contributor to the Mato Grosso Pantanal. . The present study analyzed the environmental conditions of the Prata River Basin associated to the physiographic aspects of the basin, the use and occupation of the land and the production of the local geographic space, a geosystemic approach was used for landscape analysis, as well as technical procedures of Geographic information (GIS), all associated with field verification. As a result of the integrated environmental analysis, the geomorphological mapping with a scale of 1: 25: 000 was obtained. The physiognomies (Erosive Escarps, Coluvian Reservoirs, Eroded Surfaces, Morros Testimonies, "V" and "u" valleys, wet valleys, rocky outcrops) and current processes of laminar and mechanical erosion (76 events). These features and processes were interrelated with other physiographic aspects (pedology, geology and climatology) and land use, a factor that allowed the sectorization of four areas of distinct fragility in the BHRP. Another bias of the research was the study of the impacts that occurred at the mouth of the Prata River, which was drowned by the construction of the Zé Fernando SHPP in the São Lourenço River, a fact that caused a change in the morphometric parameters of the BHRP and a possible change in the landscape dynamics for the area study.